Effects of macromolecular configuration of thermally sensitive binder in lithium‐ion battery. Issue 31 (19th April 2017) - Le, Anh V.; Wang, Meng; Noelle, Daniel J.; Shi, Yang; Yoon, Hyojung; Zhang, Minghao; Meng, Y. Shirley; Qiao, Yu
ABSTRACT: In order to suppress heat generation of nail‐penetrated lithium‐ion battery (LIB) cell, thermally sensitive binders (TSB) based on poly(vinylidene fluoride) (PVDF) and poly(vinylidene fluoride‐ co ‐hexafluoropropylene) (PVDF‐HFP) were investigated. The testing data showed that with appropriate treatment, TSB could efficiently reduce the peak temperature associated with internal shorting, and did not influence the cycling performance of LIB. The molecular weight of TSB was not a vital factor, while crosslinking was critical. This technology can be used to mitigate thermal runaway of LIB, enabling safe and robust large‐scale energy storage. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45078. Abstract :